2012
DOI: 10.2147/ijn.s23771
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of glucose-modified liposomes using polyethylene glycols with different chain lengths as the linkers for brain targeting

Abstract: Background An intimidating challenge to transporting drugs into the brain parenchyma is the presence of the blood–brain barrier (BBB). Glucose is an essential nutritional substance for brain function sustenance, which cannot be synthesized by the brain. Its transport primarily depends on the glucose transporters on the brain capillary endothelial cells. In this paper, the brain-targeted properties of glucose-modified liposomes using polyethylene glycols with different chain lengths as the linkers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Qin and coworkers have utilized N-acetyl glucosamine (NAG) as a ligand for the GLUT1 to deliver Coumarin-6, as fluorescent probe, to brain cells (11). Moreover, Xie and coworkers demonstrated that the water solubility of NAG led to greater cellular internalization capacity of the pegylated-glycosylated liposomes (12). They have also reported that high PEG surface modification may retard the targeting capacity of the liposome to endothelial cells due to the steric hindrance, whereas low content of PEG may obstruct the exposure to GLUT receptors (12).…”
Section: Introductionmentioning
confidence: 99%
“…Qin and coworkers have utilized N-acetyl glucosamine (NAG) as a ligand for the GLUT1 to deliver Coumarin-6, as fluorescent probe, to brain cells (11). Moreover, Xie and coworkers demonstrated that the water solubility of NAG led to greater cellular internalization capacity of the pegylated-glycosylated liposomes (12). They have also reported that high PEG surface modification may retard the targeting capacity of the liposome to endothelial cells due to the steric hindrance, whereas low content of PEG may obstruct the exposure to GLUT receptors (12).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a plethora of techniques has been used to verify in vivo the preliminary results obtained with the cellbased assays, namely scintigraphy [324][325][326], near-infrared in vivo imaging [327][328][329][330][331][332][333], ex vivo optical imaging [301,334], confocal microscopy [309,317], chromatographic quantification [307,312,315,335] and pharmacodynamics studies [281,285,336]. In all cases, the consistency between the results from in vitro and in vivo studies was evidenced.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The main conclusions from the results of the studies presented in Table 7, include the fact that an increase in the size of the nanocarrier yields a decrease in the BBB permeability coefficient [297][298][299][300][301][302][303][304][305] and that nanoparticle surface plays a key role in BBB permeability (in terms of surface coating [306] and surface charge, with enhanced permeability values for cationic charges [302,307,308]). Overall, drug loading onto nanocarriers enhances BBB permeability and this enhancement often follows a timedependent pattern [309][310][311][312][313][314][315].…”
Section: Concluding Remarks On Cell-based Modelsmentioning
confidence: 99%
“…Its transport primarily depends on the glucose transporters on the brain capillary endothelial cells. Xie et al 62 showed that the glucosemodified liposomes GLU1000-LIP exhibit a strong brain delivery capacity.…”
Section: Liposomesmentioning
confidence: 99%